Implementasi Konseling Multikultural dalam Menangani Konflik Diskriminasi Bahasa di Sekolah - Delpina R. Markus Manda’; Vera Nika Lisubua’; Jeane Marieske; Ronaldo Stefanus (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze and synthesize findings from various scientific literature on the implementation of multicultural counseling as an effective intervention in addressing language discrimination conflicts in school environments. Language discrimination (linguisticism) is a social justice issue that seriously impacts the psychological well-being and academic outcomes of minority students. Unfair treatment of someone based on their language is not only a social issue but can also cause students to feel sad and stressed, and can affect their grades or academic achievement. The research method used was a Systematic Literature Review, which focused on an in-depth analysis of the concept of multicultural competence and the role of counselor advocacy in a linguistic context.  The results of this study indicate that culturally respectful counseling can be an effective method to address language discrimination, by championing changes in the school system and making counselors more sensitive to cultural differences. This study concludes that the implementation of multicultural counseling is an effective way to create a fair learning environment and respect linguistic diversity.